Sufi Dance: Spiritual Harmony for Mental Health and the Strengthening of Character Education - Dianing Pra Fitri; Zumrodi Zumrodi; Meta Malihatul Maslahat (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to examine the implementation and implications of Sufi dance in fostering mental health and its connection to education. The research was conducted at Al-Ishlah Islamic Boarding School, Semarang, employing a qualitative field research method. Data collection techniques included observation, interviews, and documentation. The subjects of this study were the founder of Sufi dance and five Sufi dancers who are students at Al-Ishlah Islamic Boarding School, Semarang. Data analysis followed the steps of data reduction, data presentation, verification, and conclusion drawing. The results of this study demonstrate that the implementation of Sufi dance imparts numerous positive values, nurturing the soul and enhancing spiritual development. This enhancement of mental and spiritual aspects contributes significantly to achieving mental health, as well as holistic well-being encompassing the bio-psycho-social and spiritual dimensions. Moreover, the values and teachings embedded in Sufi dance serve as a medium to strengthen character education and promote personal growth